On the temporal and behavioural consistency of pre-performance routines: An intra-individual analysis of elite basketball players' free throw shooting accuracy - Lonsdale, C.; Tam, J. T. M. (Journal of Sports Sciences, 2008)
The effectiveness of pre-performance routines on skilled performance in a self-paced skill has yet to be verified. In this study, we examine the importance of temporal and behavioural consistency in these routines. The duration and specific pattern of behaviours exhibited before each free throw (n = 284) were observed during 14 National Basketball Association play-off games. An intra-individual standardized score was calculated for each shot's duration. Each player's dominant behavioural routine was identified and each shot was classified as "sequence followed" or "sequence not followed". No difference was observed in the success rates of shots associated with brief, long, and regular duration routines (P > 0.05). However, players were more successful when they followed their dominant behavioural sequence (83.77% success) than when they deviated from their specific behavioural pattern (71.43% success) (P < 0.05). The findings are interpreted in light of relevant theory and implications for practice are discussed.